A hybrid connector for efficient web servers. (26th May 2009) - Carrera, David; Beltran, Vicenc; Torres, Jordi; Ayguade, Eduard
In this paper we introduce a novel web server architecture that combines the best aspects of both the multithreaded and the event-driven architectures, the two major existing alternatives, to create a server model that offers an improved performance in terms of user session completions without losing the natural ease of programming characteristic of the multithreading paradigm. We describe the implementation of this architecture on the Tomcat 5.5 server and evaluate its performance. The obtained results demonstrate the feasibility of the hybrid architecture and the performance benefits that this model introduces for e-commerce applications.